Child of God [videorecording (DVD)] - Franco, James, 1978-; Nelson, Tim Blake; Parrack, Jim; Haze, Scott; McCarthy, Cormac, 1933- ([Publisher not identified], 2014)
In 1960's Tennessee, Lester Ballard is a violent loner who has lived in the woods and caves since early childhood. He has no sense of right or wrong or how normal society operates.